Utilização de meios heterotróficos na produção de guppy (Poecilia reticulata) - Silva, Vagner Callai da (2015)
Aquaculture, an activity that is controlled cultivation of aquatic organisms such as fish, shellfish and plants, in fresh or salt water is an old activity that is standing out increasingly worldwide. However the development of this activity with the creation of new fish farms causes the increased generation of effluents that may eutrophicaion the natural environment. Thus there is a search for new alternative systems of production to remedy these environmental issues and also to increase the productivity of the animals. Based on this, the study aimed to evaluate the influence of the use of different heterotrophic media in production of Guppy (Poecilia reticulata). The animals were allotted in four treatments and four replications, with addition of water culture supplements including: T1 (control), T2 with addition of algae, T3 and algae anel bioflocos and T4 with bioflocos where the carbon nitrogen ratio was kept the same for systems with bioflocos. The water physico-chemical variables of the systems remained within the ideal standards for poecilídeos. At the end of the experiment, it was observed when analyzing the total length that treatments 2, 3 and 4 present higher average than the control animals, however the treatments 2 and 3 do not differ other. This demonstrates the efficiency of the heterotrophic in medium on the guppys production.